ARTICULATION IN SCIENCE PROGRAMMES: A PLACEMENT STRATEGY TO ENHANCE STUDENT SUCCESS. - Jacobs, M.; de Bruin, G. P.; van Tonder, S. P.; Viljoen, M. (South African Journal of Higher Education, 2015)
This article reports on the results of an investigation into the academic performance of first-year students in science and engineering programmes at the University of Johannesburg (UJ), South Africa. The increase in the drop-out rate and the decrease in the success rate in science modules such as Mathematics, Physics and Chemistry at first-year level is a serious challenge for South African higher education (HE). Science, engineering and health science faculties need to rethink admission processes, curricula and teaching and learning, as these modules form the core first-year curriculum in these fields. Placement versus selection remains a contentious issue in HE, and different admission criteria are applied in order to meet enrolment targets in higher education institutions (HEIs). This investigation suggests that post-admission placements have institutional advantages and increase the likelihood of student success. Current placement and admission practices are based on school performance. It is suggested here that the placement strategy in science-related programmes should be based on students' performance at school, the National Benchmark Test (NBT) and adaptation to HE at first-year experience. Structured articulation pathways can provide for placement into main stream, extended degree or diploma programmes and could improve graduation rates.